Economic Benefits of Green Technologies: Ukrainian Experience - Yarova, Nina; Lipych, Liubov; Gutsul, Tetiana; Zhurba, Oleksandr; Novytskyi, Vladyslav (International Journal of Economics and Financial Issues, 2024)
This study evaluates the economic benefits of implementing green technologies in Ukraine, focusing on their contribution to sustainable development, energy efficiency, and economic growth. The research aims to identify how renewable energy projects and energy-efficient technologies can enhance Ukraine’s energy security, reduce dependency on fossil fuels, and foster innovation-driven economic modernization. A multi-method approach was employed, combining a systematic literature review, statistical data analysis, and a comparative evaluation of solar and wind energy projects. The study draws on secondary data from governmental and international agencies, spanning the period 2014-2023, and utilizes descriptive statistics to assess trends in job creation, investment, and reductions in natural gas imports. The results indicate significant progress in solar and wind energy development, with total installed capacities reaching 7.6 GW and 2.4 GW respectively by 2023. Employment in green sectors exceeded 50.000 jobs, with solar energy accounting for 40% of this workforce. Investments in green technologies totaled approximately €12 billion between 2014 and 2022, stimulating economic growth and reducing Ukraine’s natural gas imports by 15%. Despite these achievements, challenges remain, including financial barriers, regulatory instability, and outdated infrastructure. However, the study highlights opportunities for further progress through policy reforms, infrastructure modernization, and international cooperation. The research concludes that green technologies are essential for Ukraine’s transition to a sustainable economy, offering both environmental preservation and economic growth potential. These findings underscore the need for policy consistency, expanded financing options, and increased public awareness to maximize the economic benefits of green technologies in Ukraine. By leveraging these innovations, Ukraine can enhance its energy independence, competitiveness, and resilience in the global market.